2014
DOI: 10.1021/ma501754u
|View full text |Cite
|
Sign up to set email alerts
|

Versatile 2-Methoxyethylaminobis(phenolate)yttrium Catalysts: Catalytic Precision Polymerization of Polar Monomers via Rare Earth Metal-Mediated Group Transfer Polymerization

Abstract: The present study is one of the first examples for rare earth metal-mediated group transfer polymerization (REM-GTP) with non-metallocene catalyst systems. 2-Methoxyethylaminobis(phenolate)yttrium trimethylsilylmethyl complexes were synthesized and showed moderate to high activities in the rare earth metal-mediated group transfer polymerizations of 2-vinylpyridine, 2-isopropenyl-2-oxazoline, diethyl vinylphosphonate, diisopropyl vinylphosphonate, and N,N-dimethylacrylamide as well as in the ring-opening polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 50 publications
6
89
0
Order By: Relevance
“…[28][29][30][31] Apart from the mentioned examples only few groups investigated the stereospecific polymerization of 2VP. 49 A correlation between the steric demand of the ortho position in the ligand structure and the activity was observed. Rare earth metal-mediated group transfer polymerization (REM-GTP) in contrast is a relatively recent polymerization method for 2VP.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…[28][29][30][31] Apart from the mentioned examples only few groups investigated the stereospecific polymerization of 2VP. 49 A correlation between the steric demand of the ortho position in the ligand structure and the activity was observed. Rare earth metal-mediated group transfer polymerization (REM-GTP) in contrast is a relatively recent polymerization method for 2VP.…”
mentioning
confidence: 89%
“…Subsequent mechanistic studies of Soum and Fontanille with organomagnesium compounds revealed that the stereocontrol derives from a Markov-chain end control through a favoured gauche coordination of two monomers to the metal cation. 49 Mechanistic studies revealed a living monometallic group-transfer polymerization mechanism and kinetic studies showed the exceptional activity for the polymerization of 2VP. [32][33][34][35][36] In addition Frustrated Lewis pair, 37,38 anionic [39][40][41][42][43][44] and radical [45][46][47][48] polymerizations have been applied to synthesize functional but atactic P2VP based materials.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction of LY(CH 2 Ph) 2 (THF) with 2-phenylpyridine in a 1:2 molar ratio in THF at 30 with the free bis(phenols) in a mixture of toluene and n-pentane. [20] M a n u s c r i p t In the course of this study, it was found that the reaction conditions play a key role in the formation of the final products. For example, reactions in THF at room temperature afforded only the unexpected fused-heterocyclic compound 8,9-dibenzyl-3,14-dimethyl8a,9-dihydro-8H-benzo [4,5] a n u s c r i p t 32 silyl complexes were also found to react with 2,6-dimethylphenyl isocyanide to yield the metalla-azirine products and with carbodiimides to generate amidinate complexes (Scheme 44).…”
Section: Heteroleptic Compoundsmentioning
confidence: 96%